Model of PE-CVD Apparatus: Verification and Simulations. (2nd June 2010) - Geiser, J.; Buck, V.; Arab, M.
Abstract : In this paper, we present a simulation of chemical vapor deposition with metallic bipolar plates. In chemical vapor deposition, a delicate optimization between temperature, pressure and plasma power is important to obtain homogeneous deposition. The aim is to reduce the number of real-life experiments in a given CVD plasma reactor. Based on the large physical parameter space, there are a hugh number of possible experiments. A detailed study of the physical experiments in a CVD plasma reactor allows to reduce the problem to an approximate mathematical model, which is the underlying transport-reaction model. Significant regions of the CVD apparatus are approximated and physical parameters are transferred to the mathematical parameters. Such an approximation reduces the mathematical parameter space to a realistic number of numerical experiments. The numerical results are discussed with physical experiments to give a valid model for the assumed growth and we could reduce expensive physical experiments.